Use of Audio Devices to Increase Preventive Health Behavior during Dental Visits - Ab Malik, Normaliza; Jaafar, Azlan; Hashim Ali, Aws; Helma Mohd, Rusyda; Abdul Kadir, Nor Ba'yah (Makara Journal of Health Research, 2022)
Background: Compliance with preventive health behavior is crucial during dental visits. This study investigated using an audio device to increase dental patients’ preventive health behavior. Methods: A randomized control study was conducted in private dental practices. The test group listened to an audio device containing public health messages related to COVID-19 and preventive health behavior. The control group listened to relaxing instrumental music with no public health messages. Results: A total of 65 participants (age 18–77 years) were allocated to each group. About 63% of the participants in the test group performed preventive health behaviors compared to the control group, but the difference was not significant. Significant differences in preventive health behavior were observed in both groups before and after treatment (p < 0.001). A significant difference in the awareness level was detected between the test and control group (p < 0.01). No significant differences were found in the knowledge and self-efficacy scores between the two groups (p > 0.05). Conclusions: An audio device used during dental treatment effectively delivered public health messages to improve preventive health behavior. Hence, an audio device can be used as alternative media to deliver public health information during dental visits.